2005
DOI: 10.1007/bf03033780
|View full text |Cite
|
Sign up to set email alerts
|

The carbonyl scavengers aminoguanidine and tenilsetam protect against the neurotoxic effects of methylglyoxal

Abstract: Advanced glycation end products (AGEs) have been identified in age-related intracellular protein deposits of Alzheimer's disease (amyloid plaques and neurofibrillary tangles) and Parkinson disease (Lewy bodies), suggesting that these protein deposits have been exposed to AGE precursors such as the reactive dicarbonyl compound methylglyoxal. In ageing tissue and under diabetic pseudohypoxia, intracellular methylglyoxal levels rise through an impairment of triosephosphate utilization. Furthermore, methylglyoxal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Glycation of proteins has been implicated in the development of diabetic complications, including neuropathy, nephropathy, retinopathy and cataract (Ahmed et al, 1997;Brownlee, 1994) and other health disorders such as atherosclerosis (Kume et al, 1995), Alzheimer's disease (Vitek et al, 1994;Webster et al, 2005) and normal aging (Brownlee, 1995;Webster et al, 2005), which mainly arise from accumulation of advanced glycation endproducts (AGEs) in vivo. It is well recognized that AGE formation inhibitors can be used to retard the pathological process of the above health disorders, particularly diabetic complications, and scientists have been constantly searching for effective inhibitors of this sort.…”
Section: Introductionmentioning
confidence: 99%
“…Glycation of proteins has been implicated in the development of diabetic complications, including neuropathy, nephropathy, retinopathy and cataract (Ahmed et al, 1997;Brownlee, 1994) and other health disorders such as atherosclerosis (Kume et al, 1995), Alzheimer's disease (Vitek et al, 1994;Webster et al, 2005) and normal aging (Brownlee, 1995;Webster et al, 2005), which mainly arise from accumulation of advanced glycation endproducts (AGEs) in vivo. It is well recognized that AGE formation inhibitors can be used to retard the pathological process of the above health disorders, particularly diabetic complications, and scientists have been constantly searching for effective inhibitors of this sort.…”
Section: Introductionmentioning
confidence: 99%
“…Various AGE inhibitors that inhibit Amadori adduct formation have been designed. For example, pyrraline was attached to sugar-derived moieties of glycated proteins and thereby blocked the reactive sites from further polymerization reactions [100,101]. Similarly, penicillamine has also been reported to decrease the formation of Amadori products [102,103] and reduce the AGE levels [104].…”
Section: Therapy For Age-mediated Neurodegenerative Diseases With Synmentioning
confidence: 99%
“…While there is a report demonstrating that it was much higher (around 400 μM) (16), it was shown that blood MGO level is approximately 33.6 μM in adult SHR compared with 14.2 μM in age-matched Wistar Kyoto rats (WKY) (17). Increased level of blood MGO-derived AGEs seems to be associated with diabetic microvascular complications such as diabetic nephropathy (19), retinopathy (20), and neurological disorders (21). MGO is also known as a reactive oxygen species (ROS) inducer and impairs tissues of diabetic rats such as kidney (22), lenses (23), neuron (21), and heart (24).…”
Section: Introductionmentioning
confidence: 99%
“…Increased level of blood MGO-derived AGEs seems to be associated with diabetic microvascular complications such as diabetic nephropathy (19), retinopathy (20), and neurological disorders (21). MGO is also known as a reactive oxygen species (ROS) inducer and impairs tissues of diabetic rats such as kidney (22), lenses (23), neuron (21), and heart (24). In addition, we have recently demonstrated that glyoxal and MGO are more powerful inducers for large vascular endothelial inflammatory injury than AGEs and glucose itself (25,26), suggesting that it may be involved in the pathogenesis of large vascular complications including atherosclerosis and hypertension.…”
Section: Introductionmentioning
confidence: 99%